European Certificate of Succession: Array - Tudose, Maricica; Ion, Carmen (Journal of Danubian Studies and Research, 2021)
The theme aims at familiarizing readers with the knowledge of the European Certificate of Heir. As part of our scientific approach, we sought to shed more light on the chosen article by setting out the elements of inheritance law at both the national and European levels. Here, in the context of globalization and the dynamics of relations under private international law, especially in matters of succession, it is absolutely necessary to develop a legislative framework at the European level capable of regulating a legal document with the value and skills of an heir certificate. The purpose of the certificate is that it may be used by heirs, binders with direct inheritance rights, and by executors or estate managers who must prove their status in another Member State or exercise that right of inheritance. heir or binder and/or the functions of executor or administrator of the estate.